Prevalence and Contributing Factors of Household Food Insecurity in Somalia: A Household‐Level Analysis - Hassan Abdi Ahmed; Edwin Tito Magoti (Food Safety and Health, 2026)
ABSTRACT Somalia continues to experience a high burden of household food insecurity driven by recurrent climate shocks, protracted conflict, economic instability, displacement, and limited access to livelihoods and essential services. This study assessed the prevalence, spatial distribution, and drivers of household food insecurity using data from the 2022 Somalia Household Budget Survey. A cross‐sectional analysis was undertaken among 7152 households, and household food insecurity was measured using the Food Insecurity Experience Scale (FIES). Multivariable logistic regression identified factors associated with moderate or severe household food insecurity. Overall, 44.07% of households experienced moderate or severe food insecurity. Female‐headed households (AOR = 0.775), household heads aged 30–64 years (AOR = 0.719) and ≥ 65 years (AOR = 0.716), never‐married household heads (AOR = 0.489), and households owning nonagricultural assets (AOR = 0.666) had lower odds of food insecurity. Conversely, illiterate household heads (AOR = 1.969), households without remittances (AOR = 1.208), households receiving aid assistance (AOR = 1.699), households with access to credit (AOR = 2.116), and rural households (AOR = 1.700) had higher odds of food insecurity. Regional disparities were also observed. These findings underscore the need for targeted interventions to address demographic, socioeconomic, and geographic inequalities and strengthen household food security.